Home bias persistence in foreign direct investments. Issue 8 (14th July 2016) - Levis, Mario; Muradoǧlu, Yaz Gülnur; Vasileva, Kristina
Abstract : The purpose of this paper is to analyse the issues related to home bias and foreign direct investments (FDIs). We study the role of physical, cultural, and institutional distances from home on FDI decisions taken by corporations to assess whether the globalization of the past two decades has reduced their influence. Using the 'home bias' framework from the finance literature and the gravity model from the economics literature, we utilize a large sample of both developed and emerging markets, using FDI flows of 6263 unique bilateral country pairs over a 30-year period. We find strong empirical evidence of persistent home bias in FDI outflows, and we show that not only physical distance but also cultural and institutional similarities between host and source countries remain a decisive factor in foreign corporate investment decisions. We also show that such home bias is persistent over time and is observed around the world.